Knowledge & Factors Associated with Polycystic Ovarian Syndrome among Reproductive Age Group Women of Selected Rural Versus Urban Areas of Vadodara - Patel, Vruti; Pandya, Rachana; Patel, Hetal (International Journal of Psychosocial Rehabilitation, 2020)
Background of the Study: Polycystic ovaries are slightly larger than normal ovaries and have a number of follicles (small cysts). Polycystic ovarian syndrome produces symptoms in approximately 5% to 15% of women of reproductive age, 16 to 35 years old. The prevalence of polycystic ovarian syndrome depends on the choice of diagnostic criteria. About 18% of women had PCOS, and 70% of them were previously undiagnosed. Aims: The aim of the study was to compare the knowledge & factors associated with polycystic ovarian syndrome among reproductive-age women in selected rural versus urban areas of Vadodara. Material and Methods: A cross-sectional comparative descriptive survey design and quantitative approach were adopted to achieve the goal of the study. The study was conducted at three villages of Waghodia taluka and two urban areas of Vadodara, Gujarat. A total of 200 reproductive-aged women were recruited 100 subjects taken in each group by the non-probability convenient sampling method. Self-structured knowledge questionnaires and checklists were utilized to assess knowledge and factors associated with PCOS. Result: Out of 200 subjects, the prevalence of PCOS was 12.3% (24). The mean percentage of knowledge score in urban women was 58.8%, while in rural women it was 43.86%. Majority Factors associated with polycystic ovarian syndrome in reproductive-age women. The researchers have identified that abnormal hair growth, family history of diabetes, acne, irregular menstruation, BMI > normal, and high-calorie diets are more prevalent factors among subjects. More than 3/5 of urban women have factors associated with PCOS, and 2/5 of rural women have factors associated with PCOS. Conclusion: The study concluded that women from urban areas had more knowledge as compared to those from rural areas. Frequency of factors associated with PCOS also found to be high in urban settings.